2010
DOI: 10.2214/ajr.09.2490
|View full text |Cite
|
Sign up to set email alerts
|

CT Characteristics of Lung Nodules Present at Diagnosis of Extrapulmonary Malignancy in Children

Abstract: Lung nodules in children with extrapulmonary malignancies showed a variety of patterns on CT. In the subgroup of lung nodules that underwent biopsy, none of the nodule features studied on CT reliably differentiated benignity from malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 26 publications
4
44
0
Order By: Relevance
“…In contrast, the results of our study show that other imaging features (shape, margin, attenuation, location, and the presence of calcification and cavitation) of pulmonary nodules detected on CT studies are not helpful for predicting which pulmonary nodules are malignant in children. The results of our study correlate well with findings from a previous study that investigated the CT characteristics of pulmonary nodules present at diagnosis of extrapulmonary malignancies in children [9]. In their study, Silva et al [9] showed that pulmonary nodules in children with extrapulmonary malignancy demonstrated a variety of patterns on CT and none of the CT features could reliably differentiate benignity from malignancy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, the results of our study show that other imaging features (shape, margin, attenuation, location, and the presence of calcification and cavitation) of pulmonary nodules detected on CT studies are not helpful for predicting which pulmonary nodules are malignant in children. The results of our study correlate well with findings from a previous study that investigated the CT characteristics of pulmonary nodules present at diagnosis of extrapulmonary malignancies in children [9]. In their study, Silva et al [9] showed that pulmonary nodules in children with extrapulmonary malignancy demonstrated a variety of patterns on CT and none of the CT features could reliably differentiate benignity from malignancy.…”
Section: Discussionsupporting
confidence: 88%
“…The results of our study correlate well with findings from a previous study that investigated the CT characteristics of pulmonary nodules present at diagnosis of extrapulmonary malignancies in children [9]. In their study, Silva et al [9] showed that pulmonary nodules in children with extrapulmonary malignancy demonstrated a variety of patterns on CT and none of the CT features could reliably differentiate benignity from malignancy. Similar to their results, none of the features of the pulmonary nodules investigated showed association with the presence of underlying malignancy in our study, with the exception of nodule size.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Due to its greater sensitivity for small lesions and precision for measuring the size of lesions, CT is routinely used in follow-up of treated malignancy. While CT is highly sensitive, it lacks specificity and cannot reliably differentiate between benign and malignant lung nodules (McCarville et al 2006;Silva et al 2010). Correlation with clinical history and serial imaging follow-up improves its specificity.…”
Section: Imagingmentioning
confidence: 99%
“…Yet the detection of incidentalomas occurs with relative frequency in children as well (mainly adrenal [10] and pulmonary in origin [11]), presumably related to the increase in the use of pediatric CT in recent years [12,13]. This, in combination with recent rapid technological advances in CT, has allowed for the routine detection of lung nodules as small as 1-2 mm on scans that cover all or part of the chest [11,14].…”
Section: Introductionmentioning
confidence: 99%